Den armen gedeylt: Differentiaties tussen stad en dorp in de zestiende-eeuwse publieke armenzorg in de Antwerpse Kempen - Peeters, Jan (TSEG - The Low Countries Journal of Social and Economic History, 2023)
This article bridges the gap between studies of urban and of rural poverty by including both contexts it a comparative analysis. Using the accounts of the Holy Ghosttables it compares the sixteenth century poor relief between rural and urban communities in the Campine region and focusses on differences in the financing and the structure of the social expenditure, the social position of the Holy Ghostmasters and the generosity of the relief. Although surprisingly many similarities in outdoor relief existed between town and village, the extent of the relief was significantly higher in the Campine cities of Herentals and Hoogstraten than in the neighbouring villages. Not the different power structures or degrees of social cohesion and inequality but the scale of the local urban economies and the surplus capacity of the urban middles classes explain these differences.